Pre and Post-Weaning Performance Characteristics of Brahman, Boran and Tuli Crosses in Beef Cattle Evaluation Programs - K. J. Rowan; D. G. Taylor; M. J. Josey (Buletin Peternakan, 1995)
Abstract dalam bentuk hard copy